2018
DOI: 10.1002/ehf2.12252
|View full text |Cite
|
Sign up to set email alerts
|

N‐terminal pro‐B‐type natriuretic peptide and prognosis in Caucasian vs. Asian patients with heart failure

Abstract: AimsN‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) is the most frequently used biomarker in heart failure (HF), but its prognostic utility across ethnicities is unclear.Methods and resultsThis study included 546 Caucasians with HF from the Coordinating Study Evaluating Outcomes of Advising and Counseling in Heart Failure and 578 Asians with HF from the Singapore Heart Failure Outcomes and Phenotypes study. NT‐proBNP was measured at discharge after HF hospitalization. The studied outcome was a composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Therefore, we did not include a control group of children without DCM, and hence, our study was not suited to evaluate hypotheses with respect to such subjects. Noteworthy, in this respect, the design of our study is similar to numerous other studies on variables carrying prognostic information in paediatric and adult heart failure 1,30,31 . Third, missing data were an issue, as may be expected in a longitudinal multicentre study in children.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, we did not include a control group of children without DCM, and hence, our study was not suited to evaluate hypotheses with respect to such subjects. Noteworthy, in this respect, the design of our study is similar to numerous other studies on variables carrying prognostic information in paediatric and adult heart failure 1,30,31 . Third, missing data were an issue, as may be expected in a longitudinal multicentre study in children.…”
Section: Discussionmentioning
confidence: 79%
“…Predicting outcome in children with dilated cardiomyopathy Noteworthy, in this respect, the design of our study is similar to numerous other studies on variables carrying prognostic information in paediatric and adult heart failure. 1,30,31 Third, missing data were an issue, as may be expected in a longitudinal multicentre study in children. NT-proBNP measurements were available in all centres except one, where BNP measurements were reported.…”
Section: Study Limitationsmentioning
confidence: 98%
“…(13,14) The demography of heart failure is significantly different between Caucasian and Asian cohorts, with the latter being younger but with higher rates of hypertension and diabetes mellitus. (15) While the prognostic value of detecting LGE on CMR imaging was established for Caucasian cohorts and meta-analyses performed, Asian case series from Japan, China and now ours from Singapore, reaffirm the identification of LGE as a powerful tool for prognostication of Asian patients with DCM. (13,16,17) It is difficult to make further comparisons between Caucasian and Asian patient series, as there is significant heterogeneity in the profiles of patients reported in each series, inclusion criteria, choice of outcome measures and duration of follow-up.…”
Section: Methodsmentioning
confidence: 84%
“…A previous study reported that despite ethnic differences in known clinical determinants of plasma NT-proBNP, it still has similar prognostic performance in Asians and Caucasians with HF. 27) Several studies have shown that NT-proBNP can be used for prognostic assessment and risk stratification in HF, which applies equally to Chinese patients; 16,27) however, it is still inconsistent whether and how the prognostic value of NT-proBNP in patients with HF is affected by obesity. A previous study found that NP levels predicted the primary outcome (death from cardiovascular causes or first hospital admission) in all BMI categories.…”
Section: Discussionmentioning
confidence: 99%